TV and Cars - Grainge, Paul 1972- (Edinburgh University Press, 2022)
Considers the social life of cars as represented on TVProvides an original thematic approach to television studies, exploring how a particular TV situation (passengering) can provide a prism on TV as a small screen mediumAnalyses comedy entertainment across genre forms, including sitcom, late-night talk show segments, web series and vloggingOffers an interdisciplinary perspective that brings together 'media studies' and 'mobility studies'Apprehends tendencies in contemporary television while offering a screen view of our cultural relationship with carsTV and Cars offers a compelling lens on television in a mobile media era. Cars are vehicles for television, a fixture of the shows and ads that drive TV. In this original approach to contemporary television, Paul Grainge looks beyond questions of speed, spoilers and cylinders to explore the small screen intimacy of cars - the way people interact, sing and dwell in the habitat of automobiles. Considering the industrial, cultural and aesthetic relation between TV and cars, Grainge examines how comedy entertainment such as sitcoms, talk shows, web series and vlogs have been drawn to the practice of 'passengering'.Getting under the bonnet of popular 'drive-and-talk' series like The Trip, Carpool Karaoke, Peter Kay's Car Share and Comedians in Cars Getting Coffee, this engaging interdisciplinary excursion finds new ways to look at both television and the social life of cars
Description based on online resource; title from PDF title page (publisher's Web site, viewed 24. Mai 2022)
Keywords: Film, Media & Cultural Studies; PERFORMING ARTS / Television / Direction & Production; Automobiles on television; Automobiles -- Social aspects